Wealth of material for the cub reporter - Mark Pearson (Asia Pacific Network, 2008)
Ten New Zealand journalism educators- all experienced journalists—have gone a long way toward meeting that challenge in this, the fourth edition of their 'Bible'—the key text for teaching the discipline to ther nationally accredited unit standards.